How religion works : towards a new cognitive science of religion - Pyysiäinen, Ilkka (Brill, 2003)
Modern findings in cognitive science and evolutionary psychology provide insights to the processes which make religious beliefs and behaviours efficient attractors in and across cultural settings. This text discusses how certain kinds of counter-intuitive ideas are selected for religious use.